PARAS INTERLEUKIN-18 PENDERITA TUBERKULOSIS PARU DAN PERAWAT SEHAT BERISIKOTUBERKULOSIS - Sianny Herawati; J Nugraha (Indonesian Association of Clinical Pathologist and Medical laboratory, 2008)
Tuberculosis is an infectious disease which is the second cause of death in the world. Indonesia belongs to the third ranks as themost prevalent tuberculosis country. However the eradication is programmed only to focus on finding the case and treatment of theactive tuberculosis patients. Health care workers are at risk to tuberculosis infection, but there is no examination yet for early detectionactivity of tuberculosis. In order to know the activity of tuberculosis, other examinations are needed such as IL-18 examination. Today, no research about IL-18 is performed yet in Indonesia; therefore this study is performed in order to know the difference of IL-18level in active tuberculosis patients and nurses at risk. This study is to know the difference between IL-18 plasma of active tuberculosispatients and nurses at risk by analysis. A cross sectional, observational analytical study of 8 nurses at risk of tuberculosis and 8 activetuberculosis patients, has been conducted from February up to April 2007, at the Dr. Soetomo General Hospital and Karang TembokHospital in Surabaya. The diagnosis of active tuberculosis patients was based on positive sputum bacteriological examination, positiveradiology examination and who never had received anti-tuberculosis drugs. Nurses at risk of tuberculosis consisted of those who had beenworking more than 2 years, and was examined by negative bacteriological and radiology examination, TB-dot and positive tuberculinskin test with a diameter – 10 mm. IL-18 examination was done by double antibody sandwich ELISA method (MBL/Medical & BiologicalLaboratories Co.Ltd). IL-18 level in active tuberculosis patients was 491.4–1215.3 pg/ml (mean 794.6 pg/ml, SD 222.6), in nursesat risk of tuberculosis was 88.9–429.0 pg/ml (mean 256.2 pg/ml, SD 137.6). There was a significant difference of IL-18 level amongactive tuberculosis patients and nurses at risk of tuberculosis (p < 0.001); the IL-18 level in active tuberculosis patients was significantlyhigher than in nurses at risk of tuberculosis.